Managing Quarterly DBP Stress in Ohio. Issue 10 (1st October 2013) - Skeriotis, Andrew T.; Miller, Christopher M.; Sanchez, Nancy
Abstract : Surface water presents many challenges for water treatment, including stricter regulation of disinfection byproducts (DBPs) mandated by the US Environmental Protection Agency's Stage 2 Disinfectants/Disinfection Byproducts Rule (D/DBPR). Crucial to utilities being in compliance with the Stage 2 D/DBPR is the ability to obtain real‐time DBP formation potential and to monitor dissolved organic carbon removal as changes are made to the treatment train.